Analisis Stres Kerja pada Pengemudi Truk Pengantar Produk PT XYZ Tahun 2022 - Oktaviana, Riska; Hendra, Hendra (National Journal of Occupational Health and Safety, 2022)
Drivers are one of the occupational groups with the highest risk of experiencing workplace stress. This can happen to truck drivers who play an important role in the PT XYZ product delivery process. This study aims to describe the work stress level in PT XYZ product delivery truck drivers and the risk factors associated with work stress. The factors studied include individual factors (age, marital status, place of residence, number of children, and length of service), psychosocial factors related to job context (job control, social support, and home-work interface), and job content (physical environment of the cabin, workload, and working hours). This study used a cross-sectional research design, and data collection was carried out by distributing online questionnaires. The questionnaires used in this study were adapted from several existing questionnaires, namely the Perceived Stress Scale (PSS-10), NIOSH Generic Job Stress Questionnaire (GJSQ), and Copenhagen Psychosocial Questionnaire (COPSOQ) III. A total of 76 truck drivers participated in this study. The results showed that 60.53% of the respondents experienced moderate-severe stress. There was also a relationship between social support, home-work interface, the physical environment of the cabin, workload, and working hours with work stress. Of the five factors, the most dominant factor associated with work stress is the working hours factor, with an OR value of 11. It is concluded that social support, home-work interface, the physical environment of the cabin, workload, and working hours have a significant relationship with work stress. Some measures that can be taken care identifying the incidence of work stress in workers are developing supervision and mentoring programs related to work stress, reviewing procedures and policies regarding work schedules, creating a physically healthy and safe workplace, identifying and reviewing workload, and implementing various intervention programs to improve workers' stress coping skills.